Pendidikan Agama Islam dan Kualitas Ekonomi Keluarga Muslim - Moh Rifai (JURNAL PROFIT, 2023)
This study aims to explore the relationship between Islamic religious education and the economic quality of Muslim families. Islamic religious education is an important aspect of Muslim life that plays a role in shaping their values, beliefs and religious practices. Meanwhile, the quality of the family economy is an important indicator to measure the welfare and sustainability of family life. The literature research method, which is also known as the literature research method, involves collecting, analyzing, and synthesizing information from various sources of literature that is relevant to answering research questions or understanding the topic under study. The results of this study indicate that there is a significant relationship between Islamic religious education and the economic quality of Muslim families. Families that have a higher level of Islamic religious education tend to have better economic quality. Islamic religious education can provide a strong moral and ethical foundation in managing family economic resources, avoiding behavior that is inconsistent with religious principles, and increasing sound financial understanding and practice. This finding has important implications for the development of Islamic religious education and programs that focus on the economic empowerment of Muslim families. Efforts to increase access to and quality of Islamic religious education can contribute to improving the economic quality of Muslim families as a whole. In addition, an approach that integrates aspects of Islamic religious education and finance can help develop financial literacy and good financial management among Muslim families. However, this study also acknowledges that there are other factors that can affect the economic quality of Muslim families, such as macroeconomic factors, level of general education, and access to economic opportunities. Therefore, further research is needed to deepen understanding of this relationship and other relevant factors.